Exploring Student Perceptions of Quizizz for TOEFL Reading Practice - Kurniawati, Devi Candra; Rasuki, Muhlisin; Nurkamilah (Scripta : English Department Journal, 2024)
This study investigates students’ perceptions of using Quizizz for reading tests in TOEFL preparation classes. The research employs a quantitative approach through a survey conducted via a closed-ended questionnaire comprising 20 items. Data were collected using Google Forms, and analysis was performed using a 5-point Likert Scale, with averages calculated in Microsoft Excel. The study assesses six aspects of student perception: attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. The overall mean percentage score for Quizizz in the reading tests of TOEFL preparation classes is 77.37%, indicating a positive reception among students. The findings suggest that students perceive Quizizz as user-friendly and effective in enhancing their interest in reading tests, preferring it over other online learning tools. Consequently, Quizizz is recommended for use in TOEFL reading preparation classes, as it promotes enthusiasm among students, positioning it as a superior Mobile Assisted Language Learning tool compared to others.